Pengaruh Good Corporate Governance dan Environmental Social Governance terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Moderasi - Siti Nur Arofah; Khomsiyah (SAFE-Network, 2023)
The faster information spreads, the more important it is for companies to publish good things and minimize issues that can have a negative impact on company reputation and value. Publication of positive information such as the application of good governance and disclosure of social responsibility among cases and issues of rampant corruption and environmental pollution is very attractive for investors to take into consideration in investing. Therefore, this study aims to examine the influence of Good Corporate Governance and Environmental Social Governance on Corporate Values ​​with Financial Performance as Moderation. This research uses a sample of 16 companies which have been listed on the Indonesia Stock Exchange for 3 consecutive years, participating in the CGPI assessment program and also the ESG Refinitiv Scores in the 2019 – 2021 period. The research sample was determined using a purposive sampling method. This type of research and data used is quantitative with secondary data. The analytical method used is panel regression analysis and moderation regression analysis. This study after being moderated by Financial Performance (ROA) can provide results that significantly strengthen the effect of Good Corporate Governance and Environmental Social Governance on Corporate Values, whereas before being moderated both have no influence on Corporate Values. This study also uses company size as a control variable.